Transportation: Making Tracks for Tomorrow’s Transportation 2002
DOI: 10.1115/imece2002-39078
|View full text |Cite
|
Sign up to set email alerts
|

Self-Pierced Rivet (SPR) Modeling in Aluminum Structure Crash Analysis

Abstract: A finite element method has been developed for modeling the characteristics of self-pierced rivets (SPR) in the aluminum parts and structures subjected to impact. It considers SPR elastic, inelastic and separation behaviors and was developed based on the coupon test results in lap shear, coach peel, and tension modes. The method consists of establishing baseline strength characteristics in the six degrees of freedom; and then modifying the baseline properties with coefficient factors (Ki) factors that influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The results showed that the mechanical performance was similar at 1, 10 and 25 m/s, but the maximum load, energy absorption and displacement were higher at 100 m/s. Tang et al [149] developed a FEM model to simulate the crash of SPR aluminium structures. It considered the elastic and inelastic deformation and the separation behaviours and the model was developed based on the coupon test results in tension, shear and peel loading modes.…”
Section: Crashworthiness Of Spr Jointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the mechanical performance was similar at 1, 10 and 25 m/s, but the maximum load, energy absorption and displacement were higher at 100 m/s. Tang et al [149] developed a FEM model to simulate the crash of SPR aluminium structures. It considered the elastic and inelastic deformation and the separation behaviours and the model was developed based on the coupon test results in tension, shear and peel loading modes.…”
Section: Crashworthiness Of Spr Jointsmentioning
confidence: 99%
“…The model for SPR was developed based on the existing model for spot welding with shell elements. The crash performance of SPR joints was studied by Tang et al [149] through simulation in RADIOSS commercial finite element code. The SPR joints were simulated as nonlinear spring elements.…”
Section: Modelling Of Spr Joined Structuresmentioning
confidence: 99%
“…This approach did not consider the residual stresses due to piercing. A FE method has been developed by Tang et al (2002) for modelling the characteristics of SPR in the aluminium parts and structures subjected to impact. It relies on a combination of baseline curves and the universal formulation that predicts the SPR performance by considering the effects of different parameters.…”
Section: Finite Element Analysis Of Spr Jointsmentioning
confidence: 99%
“…A modelling method of SPR has been developed by Tang et al [35] using test and statistical analysis of coupons in tension, shear and peel modes. It consists of establishing baseline strength characteristics in the six degrees of freedom, and then modifying the baseline properties with coefficients that influence the performance of the joint.…”
Section: Static and Fatigue Behaviour Of Spr Jointsmentioning
confidence: 99%